(3-2i)x+4i=(2+i)x+3

Simple and best practice solution for (3-2i)x+4i=(2+i)x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-2i)x+4i=(2+i)x+3 equation:


Simplifying
(3 + -2i) * x + 4i = (2 + i) * x + 3

Reorder the terms for easier multiplication:
x(3 + -2i) + 4i = (2 + i) * x + 3
(3 * x + -2i * x) + 4i = (2 + i) * x + 3

Reorder the terms:
(-2ix + 3x) + 4i = (2 + i) * x + 3
(-2ix + 3x) + 4i = (2 + i) * x + 3

Reorder the terms:
4i + -2ix + 3x = (2 + i) * x + 3

Reorder the terms for easier multiplication:
4i + -2ix + 3x = x(2 + i) + 3
4i + -2ix + 3x = (2 * x + i * x) + 3

Reorder the terms:
4i + -2ix + 3x = (ix + 2x) + 3
4i + -2ix + 3x = (ix + 2x) + 3

Reorder the terms:
4i + -2ix + 3x = 3 + ix + 2x

Solving
4i + -2ix + 3x = 3 + ix + 2x

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-1ix' to each side of the equation.
4i + -2ix + -1ix + 3x = 3 + ix + -1ix + 2x

Combine like terms: -2ix + -1ix = -3ix
4i + -3ix + 3x = 3 + ix + -1ix + 2x

Combine like terms: ix + -1ix = 0
4i + -3ix + 3x = 3 + 0 + 2x
4i + -3ix + 3x = 3 + 2x

Add '-3x' to each side of the equation.
4i + -3ix + 3x + -3x = 3 + 2x + -3x

Combine like terms: 3x + -3x = 0
4i + -3ix + 0 = 3 + 2x + -3x
4i + -3ix = 3 + 2x + -3x

Combine like terms: 2x + -3x = -1x
4i + -3ix = 3 + -1x

Reorder the terms:
-3 + 4i + -3ix + x = 3 + -1x + -3 + x

Reorder the terms:
-3 + 4i + -3ix + x = 3 + -3 + -1x + x

Combine like terms: 3 + -3 = 0
-3 + 4i + -3ix + x = 0 + -1x + x
-3 + 4i + -3ix + x = -1x + x

Combine like terms: -1x + x = 0
-3 + 4i + -3ix + x = 0

The solution to this equation could not be determined.

See similar equations:

| (w*3)*2=24 | | -6q+1.1=-16.1-1.7q | | 8m^2+17m+27=0 | | x^2+15x-44=0 | | 2r-r+7+4r= | | 16x+9=8x+49 | | 33+6x=3(-1+5x) | | 32-180=8x+10 | | 32+8x+10=180 | | 8y-8+3(2y+4)=-2(y+3) | | -(-2+-5)=x | | 1+2(6v-4)=-3(2v-1)+6v | | 88=12+5a(30-3b)+30 | | .6d+1.8=3 | | 100=5x+10 | | 3x+4=12+5x | | 11x-4=5x+8 | | 6v+4-3(-3v-3)=5(v-1) | | 2(x-4)=5x-35 | | 15m^2+16m-15=0 | | -3a-1=7 | | 3x+20=x+100 | | Z^2+10z+12=0 | | x+(2x-4)=32 | | Z^2+10z+10=0 | | 3x-4=8+2x | | (x^3+x)(2x^2-3x-2)=0 | | h^2+5h+6=0 | | 6(t-7)+2(5t+3)=15(t-2)-2 | | 2b+3r=16 | | 7x+18+2x=180 | | -80x(x)=162 |

Equations solver categories